Impact of COVID-19 on women living with HIV who are survivors of intimate partner violence - Xinyi Zhang; Carolina R. Price; Alexandrya S. Pope; Tami P. Sullivan; Jaimie P. Meyer (BMC, 2024)
Abstract Background Women living with HIV (WLWH) experience higher rates of intimate partner violence (IPV) compared to women without HIV, but there has been minimal research to date on the impact of the COVID-19 pandemic on the lived experiences of WLWH who are IPV survivors. Methods This is a secondary analysis of COVID-19 impact using baseline data from an ongoing, prospective, micro-longitudinal cohort study of HIV care engagement among WLWH who have experienced lifetime IPV. We measured the impact of COVID-19 along key domains (i.e., physical health, day-to-day life, sexual/relationship behavior, substance use, HIV care, mental health, financial status, and having conflict with partners). Using independent t-tests or Fisher's exact tests, and Pearson's chi-squared tests, we compared women with and without ongoing IPV across sociodemographic characteristics, psychiatric disorders, substance use, and COVID-19 impact domains. We then built separate multivariate linear regression models for each of the different COVID-19 impact domains; ongoing IPV exposure was the primary explanatory variable of interest. Results Enrolled participants (n = 84) comprised a group of women (mean age 53.6y; SD = 9.9) who were living with HIV for a mean 23.3 years (SD = 10), all of whom had experienced lifetime IPV. Among 49 women who were currently partnered, 79.6% (n = 39) reported ongoing IPV. There were no statistically significant differences between those experiencing ongoing IPV and those who were not (or not partnered) in terms of demographic characteristics, substance use, or mental health. In multivariate models, ongoing IPV exposure was not associated with any COVID-19 impact domain. Anxiety and depression, however, were associated with COVID-19-related physical health, HIV care, and relationship conflict. Hispanic ethnicity was significantly associated with COVID-19-related physical health. More severe cocaine and opioid use were also significantly associated with COVID-19-related impact on day-to-day life. Conclusions Among this sample of WLWH who are all lifetime IPV-survivors, nearly half had ongoing IPV exposure. The COVID-19 public health emergency period affected WLWH in varied ways, but impacts were most profound for women experiencing concurrent mental health and substance use problems. Findings have important implications for future interventions to improve women's health and social outcomes.